Changing trends in idiopathic retinal vasculitis in a tertiary eye care centre of Nepal over a ten-year period - Kharel, R Sitaula; Aryal, S; Joshi, S N; Shrestha, J K (Nepalese Journal of Ophthalmology, 2012)
Objectives: To study the demographic profile, clinical presentations, management and visual outcome of retinal vasculitis in a tertiary eye care center of Nepal Materials and methods: A retrospective, record based study of retinal vasculitis cases in the retina clinic of a tertiary care centre in Nepal from January 2009 to January 2011 was carried out. Results of the study were compared to those from the study conducted in a similar set- up between 1998 and 2000. Results: Sixty-nine eyes of 51affected patients were evaluated in the study. The male/female ratio was 2.64:1 vs 19:1 a decade ago (p=0.0027). The mean age of the patients was 33.53 ± 12.29 years in the present study. Bilateral ocular involvement was present in 18 cases (35.3%) vs 56.14% in the past decade (p=0044).The common symptoms were dimness of vision (29.4%), floaters (25.5 %) and flashes of light (3.92%). Seventy-one eyes (69.6%) had the best corrected visual acuity of 6/18 or better. Four eyes (3.92 %) had no light perception. Vascular sheathing was the most common finding (32.35%), followed by vitritis (30.39%). Corticosteroids were primarily used to manage retinal vasculitis (39.21%). No association of retinal vasculitis with tuberculosis was found. Conclusion: The demographic pattern and clinical presentation of idiopathic retinal vasculitis has changed over a decade period in Nepal. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6541 Nepal J Ophthalmol 2012; 4 (2): 256-262